2010
DOI: 10.1038/leu.2010.175
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of patients with relapsed/refractory multiple myeloma with lenalidomide and dexamethasone with or without bortezomib: prospective evaluation of the impact of cytogenetic abnormalities and of previous therapies

Abstract: We prospectively studied the impact of several cytogenetic abnormalities (CAs) in patients with relapsed/refractory myeloma who received lenalidomide and dexamethasone (RD) with or without the addition of bortezomib (V). On the basis of the presence of previous neuropathy, 50 patients were treated with RD and 49, without preexisting neuropathy, with VRD. The overall response rate was 63%, similar for RD and VRD. Poor risk cytogenetics were associated with lower response rates in RD (P ¼ 0.01), but not in VRD (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
107
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 107 publications
(111 citation statements)
references
References 39 publications
4
107
0
Order By: Relevance
“…Until recently, risk classification did not impact on treatment decisions. However, data show that, compared with two-drug combinations, three-drug combinations improve outcomes for patients with high-risk cytogenetic abnormalities (CAs) (Stewart et al, 2015;Moreau et al, 2016a;Lonial et al, 2015a;Dimopoulos et al, 2010). For patients with high-risk CAs, aggressive therapy should be used to prevent the emergence of resistant clones.…”
Section: Patients With High-risk Cytogenetic Abnormalitiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Until recently, risk classification did not impact on treatment decisions. However, data show that, compared with two-drug combinations, three-drug combinations improve outcomes for patients with high-risk cytogenetic abnormalities (CAs) (Stewart et al, 2015;Moreau et al, 2016a;Lonial et al, 2015a;Dimopoulos et al, 2010). For patients with high-risk CAs, aggressive therapy should be used to prevent the emergence of resistant clones.…”
Section: Patients With High-risk Cytogenetic Abnormalitiesmentioning
confidence: 99%
“…A prospective study assessing the impact of cytogenetics on treatment outcome with bortezomib in combination with lenalidomide and dexamethasone found that for patients receiving bortezomib, there was no difference in ORR between those with high-risk CAs and those with standard-risk cytogenetics (P = 0.219) (Dimopoulos et al, 2010). However, in the control group (lenalidomide plus dexamethasone), the ORR was significantly lower for patients with highrisk CAs than for those with standard-risk cytogenetics (P = 0.01) (Dimopoulos et al, 2010).…”
Section: Patients With High-risk Cytogenetic Abnormalitiesmentioning
confidence: 99%
“…According to a previous study, 24 4 miRNAs, miR-152, miR15a, miR34a, and miR-223 were found to be downregulated (False discovery rate, FDR < 0.05) in the MM group compared to the non-MM group using a miRNA array. To validate this finding in our set of experiments, we performed qRT-PCR to detect the change of expression of these 4 microRNAs in B cells from 16 healthy donors and 18 primary human multiple myeloma samples.…”
Section: Expression Of Mir-152 Is Downregulated In MM Patientsmentioning
confidence: 99%
“…2 There are several combinations of drugs such as melphalan, prednisone, bortezomib, lenalidomide, dexamethasone and thalidomide that are available as front line agents for MM. [3][4][5] Only few patients are eligible for chemotherapy followed by stem-cell transplantation. 6 Often, high-dose therapies are associated with fatal complications and relapse of MM.…”
Section: Introductionmentioning
confidence: 99%
“…25 The value of stem cell transplant for chronic lymphatic leukemia is well documented. 26,27 Waldenströ m macroglobulinemia lacks the typical adverse cytogenetics 28 that are associated with diseases in which autologous stem cell transplant is regularly contemplated such as multiple myeloma. At diagnosis, À17p deletion is distinctly uncommon.…”
Section: Why Consider a Transplant In This Disease?mentioning
confidence: 99%